The Role of Productivity in Community Success: The Jesuit-Guaraní Cultural Confluence - David Satterlee (Smashwords Edition, 2013)
(Note: This material appeared previously in "Chum For Thought: Throwing Ideas into Dangerous Waters" by the same author.) This historical essay, drawn from the deepest jungles of Uruguay in South America, examines the creation of a flourishing culture and economy that lasted for almost two centuries. It explores the guided development of a virtuous web of social and economic controls that mixed the philosophy of Catholic Jesuit missionaries with the traditions of the native Guaraní peoples. An unprecedented experiment in progressive community-building may have once created that rarest of cultural treasures - a functional and stable utopia... ended only by outside pressures of conquest and exploitation. This is a living parable for our changing world, now suffering from seemingly-intractable political, cultural and economic turmoil... and struggling to be born into a tenuous future on uncertain threads of hope and despair. Rapid introduction of technology, educational systems, health care systems and social order have succeeded before - balancing competition and consumption in a new kind of community - and might be made to work again as we seek to create our own "new economy." In this startling synthesis, Mr. Satterlee brings together and introduces: • historical records, • the social theories of the Catholic Church, • the management theories of Peter Drucker, • the psycho-social theories of Don Beck's Spiral Dynamics Integral, and • the economics ideas of William Lewis and the McKinsey Global Institute on "the power of productivity."